Human Resource Management Strategy in Building an Innovative and Competitive Organizational Culture at PT. Pelabuhan Kepri - Muhammad Ferdi; Muhammad Ramadanissa; Risti Adrevi Suhela; Salva Dwi Dharma; Satriadi Satriadi (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2025)
This study aims to analyze the HR management strategy in building an innovative and competitive organizational culture at PT. Pelabuhan Kepri. The study uses a qualitative descriptive method with data collection techniques through observation, interviews, and documentation. The results of the study indicate that the main strategies implemented include competency-based recruitment, HR development through continuous training, implementation of a fair reward and punishment system, and increased internal communication to encourage collaboration and creativity. In addition, visionary and adaptive leadership is also a key factor in forming an innovative culture in the company. With this strategy, PT. Pelabuhan Kepri can build a more dynamic work culture, encourage innovation, and increase competitiveness in the port industry.